Long-Term Clinical Results of Double Bundle Reconstruction of the Medial Patellofemoral Ligament for Patellar Instability - Zhang, Lei; Li, Zhiyao (The Journal of Knee Surgery, 2019)
Medial patellofemoral ligament (MPFL) reconstruction is a satisfactory technique for patellar instability, and the anatomical double bundle variant is recommended for better clinical results. However, long-term outcomes are still uncharacterized. This study aimed to assess the effectiveness of double bundle reconstruction of the MPFL for patellar instability by means of established scores. A total of 68 patients with chronic patellar instability who underwent surgery from May 2005 to February 2010 were included prospectively. Anatomical double reconstruction of the MPFL with the semitendinosus tendon was conducted. Tegner Activity Scale (TAS), Kujala score, Lysholm knee score, and objective physical examination were assessed during follow-up. Median follow-up time for the patients was 8 (range, 6–10) years. Eight patients were lost to follow-up after 2 years. Preoperative mean TAS was 2.85 ± 0.78, increased to 4.91 ± 0.84 at 6 months and 7.26 ± 0.78 at 2 years postoperatively, and was 7.82 ± 0.89 at last follow-up. At last follow-up, pain free at rest was achieved in all patients; and 8 patients had knee pain in activities of daily living. Mean Kujala score was 57.53 ± 8.59 preoperatively, and increased to 61.22 ± 6.46, 89.51 ± 3.90, and 88.92 ± 3.84 at 6 months, 2 years postoperatively, and at last follow-up, respectively. Lysholm scores were also increased from preoperative values of 43.53 ± 10.20 to 58.22 ± 6.80, 89.37 ± 4.38, and 89.67 ± 4.13 at 6 months, 2 years postoperatively, and at last follow-up, respectively. Range of motion was 121.44 ± 12.69, 129.71 ± 6.39, 130.93 ± 5.67, and 130.78 ± 5.80 at preoperative point, 6 months, 2 years postoperatively, and at last follow-up, respectively. Long-term clinical results of double bundle reconstruction of the MPFL for patellar instability were encouraging.
Keywords: patellar instability; medial patellofemoral ligament; knee; arthroscopy